2011
DOI: 10.2109/jcersj2.119.968
|View full text |Cite
|
Sign up to set email alerts
|

Use of melamine in the nitridation of aluminum oxide to aluminum nitride

Abstract: By using melamine as a nitridizing reagent, aluminum nitride (AlN) powders were prepared from ¤-and ¡-alumina (Al 2 O 3 ) powders which had not been mixed with carbon. The hydrogen cyanide (HCN) formed by thermal decomposition of melamine was involved in the nitridation of Al 2 O 3 to AlN. The nitridation process of alumina to AlN was monitored by powder X-ray diffraction patterns and 27 Al magic-angle spinning nuclear magnetic resonance spectroscopy. ¤-Al 2 O 3 began to be converted to AlN at 1050°C without ¤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…indicated that δ‐Al 2 O 3 converted to AlN without δ‐α alumina transformation. The change in XRD patterns with calcination temperatures was similar to that when using CH 3 CN or melamine except that the sample at 1000°C showed intense AlN peaks.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…indicated that δ‐Al 2 O 3 converted to AlN without δ‐α alumina transformation. The change in XRD patterns with calcination temperatures was similar to that when using CH 3 CN or melamine except that the sample at 1000°C showed intense AlN peaks.…”
Section: Resultssupporting
confidence: 57%
“…The gases evolved at 900°C were NH 3 , HCN, and CO, while the gases evolved at 1200°C were HCN and CO. These gases were also observed for the nitridation of Al 2 O 3 using melamine . The CO gas would be evolved by the reaction between δ‐Al 2 O 3 and thermal decomposition products of PCN at the hot zone.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…However, the raw material itself has abundant oxygen elements. Therefore, melamine (C 3 H 6 N 6 ) was additionally injected into the thermal plasma jet to prevent the oxidation of decomposed Ga into Ga 2 O 3 [ 21 , 22 ]. In order to improve the crystallinity of synthesized GaN, products from the thermal plasma were subjected to annealing using a vacuum furnace.…”
Section: Introductionmentioning
confidence: 99%